1998
DOI: 10.1176/ps.49.10.1330
|View full text |Cite
|
Sign up to set email alerts
|

Case Management and Recidivism of Mentally Ill Persons Released From Jail

Abstract: This study found hopeful signs that expanding access to case management, both inside and outside jail, will help mentally ill people live in their communities and stay out of jail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 16 publications
0
62
0
4
Order By: Relevance
“…Active and continuous mental health treatment is the best defense against relapse, as well as the best offense for recovery. In turn, relapse prevention protects against recidivism (Beck & Maruschak, 2001;Monahan et al, 2001;Solomon, Draine, & Meyerson, 1994;Ventura, Cassel, Jacoby, & Huang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Active and continuous mental health treatment is the best defense against relapse, as well as the best offense for recovery. In turn, relapse prevention protects against recidivism (Beck & Maruschak, 2001;Monahan et al, 2001;Solomon, Draine, & Meyerson, 1994;Ventura, Cassel, Jacoby, & Huang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that case management services for substance use and psychological distress can attenuate the link between homelessness and incarceration. [15][16][17][18] The overall significance and scope of this issue was eloquently stated by Kushel and colleagues in their evaluation of the "revolving door" of homeless incarceration, [16] "High rates of imprisonment among homeless populations may be the end result of a system that does not provide access to timely services, including access to housing, health care, mental health care, and substance abuse treatment, and systems that have obstacles preventing receipt of these services by people exiting prison" (p. 1751). Thus, individuals who leave jail and return to the community without stable housing are at increased risk for premature mortality, [19,20] and re-arrest, [10,12] and are critically in need of interventions that increase access to services.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, individuals who leave jail and return to the community without stable housing are at increased risk for premature mortality, [19,20] and re-arrest, [10,12] and are critically in need of interventions that increase access to services. [15] Case Management Case management is the professional coordination of individualized care. [21] Specifically, case managers link individuals with relevant services and help them to overcome barriers to service utilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations